Aktivitas Antimalaria Ekstrak Sargassum Duplicatum terhadap Plasmodium Berghei Strain ANKA Secara in Vivo - Distance B Maatita; Abdul M Ukratalo; Dodikrisno E Manery (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Malaria is a parasitic infection disease caused by Plasmodium and is a global health issue. The search for new antimalarial drugs from natural sources, such as plants, is ongoing to find effective alternatives. Sargassum duplicatum, a brown seaweed, has been known to possess various biological activities; however, its antimalarial potential has not been thoroughly explored. This study aims to evaluate the antimalarial activity of S. duplicatum extract against Plasmodium berghei strain ANKA in vivo in mice. This is an experimental study. A total of 16 mice were divided into 4 groups: a positive control group and groups infected with P. berghei and treated with S. duplicatum extract at doses of 10, 100, and 200 mg/g body weight. Antimalarial activity was measured based on parasitemia levels, percent inhibition, and ED50 values. Parasitemia measurements were taken from day 0 to day 6 after treatment. The results showed that S. duplicatum extract inhibited the growth of P. berghei with parasitemia inhibition percentages of 65.32% at a dose of 10 mg/g body weight, 65.92% at a dose of 100 mg/g body weight, and 86.61% at a dose of 200 mg/g body weight. The ED50 value of S. duplicatum extract was 2.770 mg/kg body weight in mice. The low ED50 value indicates the extract’s potential as a promising antimalarial drug candidate.